2019
DOI: 10.1186/s42269-019-0128-4
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal efficacy of nano zeolite against Tribolium confusum (Col., Tenebrionidae) and Callosobruchus maculatus (Col., Bruchidae)

Abstract: Background: Stored-product insect pests are responsible for considerable quantitative and qualitative losses of agricultural products mainly cereals and legumes. The confused flour beetle Tribolium confusum and the cowpea weevil Callosobruchus maculatus are considered as the most destructive pests of stored grains and grain-derived products. In the present study nano zeolite (40-50 nm) was applied at different dose rates to wheat and cowpea to evaluate its insecticidal efficacy against both insects. Results: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
(25 reference statements)
2
3
0
Order By: Relevance
“…Nevertheless, Katroju et al 2017 concluded that, silicon dioxide and silica NPS at 0.5 and 0.25 g/kg against cigarette beetle Lasioderma serricorne (Fabricus) caused higher mortality, reduced oviposition and adults emergence and has a great promise in cigarette beetle management. The findings obtained in the current study explained that all three forms of silica had deterrent action against the three tested immature stages of C.maculatus at all concentrations used, the youngest stage (egg) was most susceptible followed by larvae and pupae .In this regard (Ibrahim and Salem 2019) declared that, reduced adult longevity, oviposition, with adverse negative effect on eggs subsequently the % of emergence of C.maculatus adults were reduced affected by Zeolite nanoparticles as well as Rouhani et al (2012) reported that silica and silver nanoparticles were highly have a physical mode of action and act like diatomaceous earth (DEs) where, the particles absorb the insect wax layer, causing death through desiccation and to a lesser degree by abrasion (Ebeling 1971). The high insecticidal potential of Silica nanoparticles activity could be attributed to the Sio2 content and nanometer size range of the particles which increase the ratio of the surface area to volume which increased insect contact with particles leading to more cuticle desiccation and death (Masumeh and Zahra 2016).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Nevertheless, Katroju et al 2017 concluded that, silicon dioxide and silica NPS at 0.5 and 0.25 g/kg against cigarette beetle Lasioderma serricorne (Fabricus) caused higher mortality, reduced oviposition and adults emergence and has a great promise in cigarette beetle management. The findings obtained in the current study explained that all three forms of silica had deterrent action against the three tested immature stages of C.maculatus at all concentrations used, the youngest stage (egg) was most susceptible followed by larvae and pupae .In this regard (Ibrahim and Salem 2019) declared that, reduced adult longevity, oviposition, with adverse negative effect on eggs subsequently the % of emergence of C.maculatus adults were reduced affected by Zeolite nanoparticles as well as Rouhani et al (2012) reported that silica and silver nanoparticles were highly have a physical mode of action and act like diatomaceous earth (DEs) where, the particles absorb the insect wax layer, causing death through desiccation and to a lesser degree by abrasion (Ebeling 1971). The high insecticidal potential of Silica nanoparticles activity could be attributed to the Sio2 content and nanometer size range of the particles which increase the ratio of the surface area to volume which increased insect contact with particles leading to more cuticle desiccation and death (Masumeh and Zahra 2016).…”
Section: Discussionsupporting
confidence: 59%
“…Aerosil 200 nanoparticles (fumed silica with size of 5-50 nm) synthetic amorphous silica composed of (99.8% Sio2) was used as a desiccating agent to kill insects (Dorota et al 2010).Zeolite nanoparticles (aluminosilicate) can be effectively replacing chemical insecticides to protect stored grains from infestation with stored product insect pests. (Ibrahim and Salem 2019) Nanoparticles zeolite (aluminosilicate) is considered nontoxic and safe for human consumption (International Agency for Research on Cancer IARC 1997a, b). Moreover, it has been listed by Codex Alimentarious Commission (1999) as granted substance in organic food production and in plant protection.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocides such as ZnO NPs have a lower risk of resistance in insects to these nanoparticles on long term application comparing to commercial insecticides. Our result is in accordance with that of Ibrahim and Salem [41] who observed under SEM zeolite nanoparticles (<45 nm) strongly attached to the cuticle of T. confusum and C. maculatus adults, ________________________________________________ Egypt. J. Chem.…”
Section: Post Toxic Effect Of Zno Npssupporting
confidence: 91%
“…Aluminum oxide and silicon dioxide nanopesticides act by binding to the insect cuticle, followed by physico-sorption of waxes and lipids, leading to insect dehydration (Debnath et al, 2011;Arumugam et al, 2016). Nanozeolite formulation acted by attaching itself to the body of T. confusum and then caused scratching and splitting of the cuticle that ultimately led to the dehydration and mortality of the insect (Ibrahim and Salem, 2019). Stadler et al (2017) reported the toxicity of nanostructured alumina and its mode of action against S. oryzae.…”
Section: Mode Of Action Of Nanopesticidesmentioning
confidence: 99%